Neonatal Head Ultrasound: A Review and Update—Part 1. Issue 3 (September 2019) - Maller, Vijetha V.; Cohen, Harris L.
Abstract : Abstract: Ultrasound of the infant brain has proven to be an important diagnostic tool in the evaluation of neonatal brain morphology and pathology since its introduction in the late 1970s and early 1980s. It is a relatively inexpensive examination that can be performed in the isolette in the neonatal intensive care unit. There is no radiation exposure and no need for sedation. This article will discuss gray scale and Doppler techniques and findings in normal head ultrasounds of premature neonates. It will discuss intracranial pathologies noted in such neonates and their neurodevelopmental outcome.